Formulating and characterizing safe lipidic liquid crystalline nanoparticles of Atorvastatin and Oligomeric Proanthocyanidin for Atherosclerotic disease treatment - Maslizan, Mardhiah; Mat Azmi, Intan Diana; Mohamad Jaafar, Adila; Haris @ Harith, Muhammad Salahuddin (2020)
Introduction: Lipidic-based liquid crystalline (LLC) nanoparticles represents a promising platform for the design of novel drug delivery system engineered by the aqueous dispersion of self-assembled lipid nanostructures in the presence of a stabilizing agent [1]. This nanostructured aqueous dispersion comprised of either inverse hexagonal (H2), inverse bicontinuous cubic (V2), inverse discontinuous cubic (I2), and lamellar (La) phases are tailored for solubilizing various types of therapeutic molecules in highly ordered self-assembled interiors, leading to effective loading and controlled delivery of bioactive materials [2]. Atherosclerosis complications remain as the most critical causes of death, is a growing health concern that clearly require optimal treatment strategies. Approach: The current research work by our research group involved characterization study of soy phosphatidylcholine (SPC) and citric acid ester of monoglyceride (citrem) which are employed in the formation of drug loaded LLC nanostructures (Figure 1). The clinical significance of the future research work involves development of a drug delivery system comprising of particular biocompatible LLC optimized for Atorvastatin (ATV) and Oligomeric Proanthocyanidin (OPC) drug delivery, targeting to RAW 264.7 macrophages cells reduced ox-LDL uptake and lipid deposition via protein inhibition and mRNA expression of Toll-like receptor (TLR)-4 and scavenger receptor (SR)-B1. Result and discussion We investigate the physicochemical characteristics including drug calibration study, encapsulation efficiency, the nanoscale structure of LLC systems (SAXS), the average uniformity (PdI), the effective electrical charge (zeta potential) on the surface of nanoparticles and the intensity averaged particle diameter (Z -average) of the drug delivery systems. We envisage the study to be a first report on ATV and OPC encapsulation in SPC and citrem-based LLC nanoparticles for enhanced anti-atherosclerotic activity.